LncRNA BANCR Promotes Endometrial Stromal Cell Proliferation and Invasion in Endometriosis via the miR-15a-5p/TRIM59 Axis - Lixue Liu; Ru Bai; Debang Li; Bai Dai; Ya Tuo (International Journal of Genomics)
Long non-coding RNA (LncRNA) emerges as a regulator in various diseases, including endometriosis (EM). This study aims to uncover the role of long non-coding RNA BRAF-activated non-protein coding RNA (lncRNA BANCR)-mediated competing endogenous RNA mechanism in endometrial stromal cell (ESC) proliferation and invasion in EM by regulating miR-15a-5p/TRIM59. ESCs were isolated from eutopic and ectopic endometrial tissues, followed by the determination of Cytokeratin 19 and Vimentin expressions in cells. Then, expressions of lncRNA BANCR, microRNA (miR)-15a-5p, and tripartite motif-containing 59 (TRIM59) in tissues and cells were determined by real-time quantitative polymerase chain reaction or Western blot assay, and cell proliferation and invasion were evaluated by cell counting kit-8 and transwell assays. After that, the subcellular localization of lncRNA BANCR and binding of miR-15a-5p to lncRNA BANCR or TRIM59 were analyzed. LncRNA BANCR was upregulated in ectopic endometrial tissues and ectopic ESCs (Ect-ESCs). Silencing lncRNA BANCR suppressed Ect-ESC proliferation and invasion. LncRNA BANCR inhibited miR-15a-5p to promote TRIM59 expression. miR-15a-5p downregulation or TRIM59 overexpression both reversed the effects of silencing lncRNA BANCR on Ect-ESC proliferation and invasion. In summary, our findings suggested that lncRNA BANCR facilitated Ect-ESC proliferation and invasion by inhibiting miR-15a-5p and promoting TRIM59.